Comparison of equipment used to measure shear properties in equine arena surfaces. (September 2015) - Lewis, Kate; Northrop, Alison J.; Crook, Glen M.; Mather, John; Martin, Jaime H.; Holt, Danielle; Clayton, Hilary M.; Roepstorff, Lars; Peterson, Michael 'Mick' L.; Hobbs, Sarah J.
Abstract : The design of a novel apparatus, the Glen Withy torque tester (GWTT), for measuring horizontal shear properties in equine sport surfaces is described. Previous research has considered the effect of vertical loading on equine performance and injury but only limited discussion has concerned the grip or horizontal motion of the hoof. The horizontal support of the hoof by the surface must be sufficient to avoid excess slip without overloading the limb. The GWTT measures the torque necessary to twist an artificial hoof that is being pushed into the surface under a consistently applied vertical load. Its output was validated using a steel surface, then was used to test two sand and fibre surfaces (waxed and non-waxed) through rotations of 40–140°, and vertical loads of 157–1138 N. An Orono biomechanical surface tester (OBST) measured longitudinal shear and vertical force, whilst a traction tester measured rotational shear after being dropped onto the surfaces. A weak, but significant, linear relationship was found between rotational shear measured using the GWTT and longitudinal shear quantified using the OBST. However, only the GWTT was able to detect significant differences in shear resistance between the surfaces. Future work should continue to investigate the strain rate and non-linear load response of surfaces used in equestrian sports. Measurements should be closely tied to horse biomechanics and should include information on the maintenance condition and surface composition. Both the GWTT and the OBST are necessary to adequately characterise all the important functional properties of equine sport surfaces. Highlights: Grip is an important functional property of equine surfaces and an injury risk factor. Measuring rotational shear resistance or torque may aid the understanding of grip. The new equipment measured differences in torque between two equine arena surfaces. Higher torque was found on a waxed compared to a non-waxed sand and fibre surface. Quasi-static compared to dynamic loads influence the response of the surface.